Development of an RF-CMOS surface acoustic wave (SAW) resonator - Sidek, Fatini; Nordin, Anis Nurashikin; Zaghloul, M. E. (2011)
Surface Acoustic wave resonators serve as essential components in Radio Frequency (RF) electronics and transceiver circuits. SAW resonators are traditionally discrete components, fabricated on piezoelectric substrates making it incompatible with CMOS technology processes. This work proposes modeling and simulation of SAW resonators which are integrated in RF-CMOS technology. An equivalent circuit model developed specifically for RF-CMOS resonator is presented. Three design examples of these resonators are shown to demonstrate the characteristics of the resonators at different resonant frequencies. The comparison between the simulated and fabricated resonators have been presented.